Network-based social coordination of business processes. (June 2016) - Maamar, Zakaria; Faci, Noura; Sakr, Sherif; Boukhebouze, Mohamed; Barnawi, Ahmed
Abstract: This paper presents a social coordination approach that addresses the issue of conflicts over resources during business process execution. A business process consists of tasks that persons and/or machines execute. The resources, that business processes require at run-time, are sometimes limited and/or not-renewable. The approach uses a set of social relations that connect tasks/persons/machines together. These relations are the basis of developing specialized networks that capture the interactions during business process execution and are used to recommend corrective actions when conflicts over resources occur. These actions are dependent on the properties of tasks, persons and machines properties which referred to as transactional, activity, and operational, respectively. A system that demonstrates the approach is also discussed.